PERKAWINAN CAMPURAN (AMALGAMASI) ANTARA ETNIS MINANGKABAU DENGAN ETNIS JAWA Studi Kasus Di Kenagarian VII Koto Talago Kecamatan Guguak Kabupaten Lima Puluh Kota - Rosalia, Popy; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Amalgamation between Minangkabau and Javanese ethnicities in Kenagarian VII Koto Talago, Guguak District, occur because of the harmonious life of the two ethnic groups. This started when the Javanese came to the Padang Gelugur, Lunang Silaut and Sitiung areas, which are Javanese ethnic transmigration areas as well as Surinamese immigrants who returned to Indonesia, which then spread to various areas in West Sumatra. In addition to the transmigration factor, the habit of the Minangkabau people to migrate is also a driving factor for marriages between the two ethnicities. With cultural differences that are owned in a mixed marriage family will result in cultural assimilation that leads to assimilation and acculturation. The objectives of this study are (1) to determine the cultural assimilation process that occurs in mixed marriages between Minangkabau and Javanese in Kenagarian VII Koto Talago, (2) to determine the forms of cultural assimilation that occur in mixed marriages between Minangkabau and ethnic ethnic groups. Java leads to a process of cultural assimilation or acculturation in everyday life in Kenagarian VII Koto Talago. This research uses descriptive caulitative method with purposive sampling technique, and the authors found 8 informants and 2 key informants. The results show that the process of cultural assimilation that occurs in mixed marriages between Minangkabau and Javanese ethnicities which leads to the assimilation process includes aspects of language, tools and living equipment seen in terms of food and clothing choices in life and from the arts-culture aspects of the marriage ceremony. pregnancy, aqiqahan and circumcision. However, in the aspect of social organization, there is a cultural assimilation that leads to acculturation, which is seen in terms of naming and acceptance of tribes and inheriting property to children. With the cultural differences that the two ethnic groups have, the integration occurs peacefully without any dispute and conflict. Keywords: Amalgamation,Minangkabau and Javanese ethnic.